L’implantation des aires protégées au vietnam : quels impacts pour les populations locales ? Une étude de cas dans la province de Lâm Đồng - Steve Déry; Martin Tremblay (VertigO)
Since the 1960s, Vietnam, as many others Southeast Asian countries, started the implementation of a protected area network. The objective was to ensure conservation of forest ecosystems, as well as of certain sites of great environmental, historical or even cultural value. But, Southeast Asian forests are the most densely inhabited in the world. Delineating national parks or natural reserves contributed to the upheaval of territorial relations where populations were affected: with new rules to follow, livelihoods needed to be adjusted, most of the time by transforming them completely. The hypothesis that articulates this article states that, in continental Southeast Asia, particularly in Vietnam, the construction of a protected area network contributes to the marginalization of populations inhabiting near or inside territories considered for protection. Bi Doup – Nui Ba national park, in Lam Dong province of Vietnam, is used as a case study.